1985
DOI: 10.1099/0022-1317-66-7-1457
|View full text |Cite
|
Sign up to set email alerts
|

Sindbis Virus Glycoproteins Are Abnormally Glycosylated in Chinese Hamster Ovary Cells Deprived of Glucose

Abstract: SUMMARYWe have previously demonstrated that Sindbis virus infection of Chinese hamster ovary (CHO) cells altered the protein glycosylation machinery of the cell, so that both normal, full-size (nine mannose-containing) oligosaccharides and abnormal, 'truncated' (five mannose-containing) oligosaccharides are transferred from lipid-linked precursors to newly synthesized viral membrane glycoproteins. In the present studies, we have examined the precursor oligosaccharides on viral glycoproteins that were pulse-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Reduced site-occupancy of N-glycans was also shown in immunoglobulin synthesis from mouse myeloma cells at low glucose concentration (<0.5 mM; Stark and Heath 1979). Davidson and Hunt (1985) showed under-glycosylation and the presence of abnormal truncated glycans in viral proteins derived from CHO cells deprived of glucose.…”
Section: Supplementsmentioning
confidence: 80%
“…Reduced site-occupancy of N-glycans was also shown in immunoglobulin synthesis from mouse myeloma cells at low glucose concentration (<0.5 mM; Stark and Heath 1979). Davidson and Hunt (1985) showed under-glycosylation and the presence of abnormal truncated glycans in viral proteins derived from CHO cells deprived of glucose.…”
Section: Supplementsmentioning
confidence: 80%
“…It has been reported that a shortage of oligosaccharide precursors caused the addition of abnormally small oligosaccharides at the initial step of glycosylation from dolichol precursors (Davidson and Hunt, 1985;Elbein, 1987;Rearick et al, 1981). Several studies have shown that glucose limitation results in incomplete protein glycosylation.…”
Section: Discussionmentioning
confidence: 95%
“…Reduced N-glycan occupancy was also shown in immunoglobulin synthesis from mouse myeloma cells at low glucose concentration (<0.5 mM) (Stark and Heath, 1979). In addition, abnormal glycosylation was found on viral proteins derived from CHO cells grown in a glucose-limited culture (Davidson and Hunt, 1985). …”
Section: Glucosementioning
confidence: 96%